Endobronchial and surgical treatment of pulmonary carcinoid tumors: A systematic literature review. (August 2019) - Reuling, E.M.B.P.; Dickhoff, C.; Plaisier, P.W.; Bonjer, H.J.; Daniels, J.M.A.
Highlights: The treatment of pulmonary carcinoid has changed over the last decades. Tumor histology, diameter and nodal status are important prognostic factors. Selected patients can be treated with parenchyma sparing procedures. Centrally located, small intraluminal carcinoid tumors are good candidates for endobronchial therapy. Abstract: The treatment of pulmonary carcinoid has changed over the last decades. Although surgical resection is still the gold standard, minimally invasive endobronchial procedures have emerged as a parenchyma sparing alternative for tumors located in the central airways. This review was performed to identify the optimal treatment strategy for pulmonary carcinoid, with a particular focus on the feasibility and outcome of parenchyma sparing techniques versus surgical resection. A systematic review of the literature was carried out using MEDLINE, Embase and the Cochrane databases, based on the Preferred Reporting Items for Systematic Reviews and Meta-Analysis statement. Two separate searches of publications in endobronchial and surgical treatment in patients with pulmonary carcinoid, were performed. Outcomes were overall survival, disease free survival, recurrence rate, complications, quality of life, and healthcare costs. Combining the two main searches for endobronchial therapy and surgical therapy yielded 3111 records. Finally, 43 studies concerning surgical treatment and 9 studies related to endobronchial treatment for pulmonary carcinoid were included. Assessment of included studies showed that lymph node involvement, histological grade, tumor location and tumor diameter were identified as poor prognostic factors and seem to be important for patients with pulmonary carcinoid. For patients with a more favorable prognosis, tumor location and tumor diameter are important factors that can help decide on the optimal treatment strategy. Centrally located small intraluminal pulmonary carcinoids, without signs of metastasis can be treated with minimally invasive alternatives such as endobronchial treatment or parenchyma sparing surgical resection. Patients with parenchyma sparing resections should be followed with long term follow up to exclude recurrence of disease. In a multidisciplinary setting, it should be determined whether individual patients are eligible for parenchyma sparing procedures or anatomical resection. Overall evidence is of low quality and future studies should focus on prospective trials in the treatment of pulmonary carcinoid.